Design of pneumatic powered pick and place robotic ARM using arduino control system - Rubanraj Saravanan (2023)
This project is done to design and develop a pneumatic powered pick and place robotic arm using Arduino Uno control system. The main aim of this project is to develop a robotic arm using pneumatic system as an effort to introduce automation in industries for material handling system. This effort was also considered as an effective way to reduce man power and increase efficiency. The control system for the robotic arm was designed using Arduino Uno microcontroller. The wprototype designed was an articulated-arm robot with 3 DOF and 3 axes. Before determining the design of the robot, a conceptual design was developed in 2D and detailed 3D designs was created using PTC Creo. Few consideration was done on the prototype’s material, cost of making and design optimization before deciding the final design. Control system using Arduino program and electrical equipment was set up. Lastly, a full working prototype was able to be delivered at the end of the project.